2003
DOI: 10.1080/02643290342000041
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Functions in Dorsal and Ventral Simultanagnosia

Abstract: Whole report of brief letter arrays is used to analyse basic attentional deficits in dorsal and ventral variants of simultanagnosia. Using Bundesen's Theory of Visual Attention (TVA), a number of previous theoretical suggestions are formalised and tested, including primary deficit in processing more than one display element, attentional stickiness, foveal bias, and global weakness of the visual representation. Interestingly, data from two cases, one dorsal and one ventral, show little true deficit in simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 40 publications
5
53
2
Order By: Relevance
“…Our argument here is that there is a monotonic relationship between the length of time over which processes such as stimulus encoding and consolidation take place and the time at which GK responded; however, we do not assume that his reaction times exactly reflect when encoding and consolidation occur. Nevertheless we note that previous work with GK (and indeed other patients with brain lesions) has shown that information processing can be slowed (see Duncan et al, 2003), which makes it difficult to gauge exactly when binding processes would operate, since these processes may be slowed along with his general reaction times. However, the point of Experiment 3 was to provide converging evidence where we specifically manipulated the time for which stimuli are available.…”
Section: Time Course and Response Timesmentioning
confidence: 96%
“…Our argument here is that there is a monotonic relationship between the length of time over which processes such as stimulus encoding and consolidation take place and the time at which GK responded; however, we do not assume that his reaction times exactly reflect when encoding and consolidation occur. Nevertheless we note that previous work with GK (and indeed other patients with brain lesions) has shown that information processing can be slowed (see Duncan et al, 2003), which makes it difficult to gauge exactly when binding processes would operate, since these processes may be slowed along with his general reaction times. However, the point of Experiment 3 was to provide converging evidence where we specifically manipulated the time for which stimuli are available.…”
Section: Time Course and Response Timesmentioning
confidence: 96%
“…In future versions of the program package, we plan to include Posner, 1980), rapid serial visual presentation, and change detection. The program package has already been used successfully in a number of neuropsychological investigations (e.g., Duncan et al, 2003;Finke, Bublak, Dose, Müller, & Schneider, 2006;Habekost & Bundesen, 2003;Habekost & Rostrup, 2006;Hung, Driver, & Walsh, 2005;Peers et al, 2005). Moreover, a clinical version of the program package is under development, which will include norms from both healthy control subjects and different neurological and psychiatric patient populations Finke et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the pioneering study, Duncan et al (1999) showed how analysis of partial-and whole-report performance in terms of the parameters defined by TVA enables a very specific measurement of attention deficits in visual neglect patients (see also Bublak et al, 2005;. TVA-based assessment has now been used in studies of simultanagnosia (Duncan et al, 2003), integrative agnosia (Gerlach, Marstrand, Habekost & Gade, 2005), developmental dyslexia (Dubois et al, 2010), alexia (Habekost & Starrfelt, 2006;Starrfelt, Habekost & Gerlach, 2010;Starrfelt, Habekost & Leff, 2009), Huntington's disease (Finke et al, 2007), Alzheimer's disease (Bublak, Redel & Finke, 2006;Bublak et al, 2009;Redel et al, 2012), and the effects of stroke in particular parts of the brain (Habekost & Bundesen, 2003;Habekost & Rostrup, 2006, 2007Peers et al, 2005;see Habekost & Starrfelt, 2009, for a review). TVAbased assessment enables the estimation of parameters related to the span of VSTM (storage capacity of K objects), the rate of encoding into VSTM (processing capacity of C objects/s), the perceptual threshold (minimum effective exposure duration of t 0 ms), and the efficiency of selecting targets rather than distractors (selectivity α, defined as the attentional weight of a distractor divided by the attentional weight of a target).…”
mentioning
confidence: 99%